Social Critique in 1 Kings 12:1–24 - Rantung, Masarama Teguh; Mawikere, Marde Christian Stenly; Wagiu, Meily (International Journal of Education, Information Technology, and Others, 2025)
This article analyses 1 Kings 12:1–24 through the theoretical lens of Pierre Bourdieu’s theory of structuration and Paul Ricoeur’s hermeneutics of social critique. Employing a qualitative-descriptive approach with a critical case study method, data were gathered through literature review, observation, and interviews conducted within the GMIM Moria Girian Indah congregation. The findings reveal that the conflict between Rehoboam and Jeroboam was not merely a matter of personal failure but rather part of a broader struggle over capital within the arena of power. Rehoboam's downfall stemmed from his inability to manage cultural and social capital effectively, whereas Jeroboam succeeded through prophetic legitimacy and popular support. The congregation’s reading of the biblical text is shaped by their respective habitus, reflecting their socio-economic dynamics and daily lived experiences. The biblical passage thus functions as a social mirror and a tool for critical reflection on the contemporary realities of the congregation.